Medicinal Plants for Management of Insomnia: A Systematic Review of Animal and Human Studies - Ayati, Mohammad Hossein; Feizi, Faezeh; Namazi, Nazli; Rahimi, Roja (Galen Medical Journal, 2019)
Insomnia is one of the most troubling sleep disorders and can be characterized by an inability to fall asleep and/or inadequate sleep duration and/or waking up multiple times during the night. Herbal medicine has been used to treat a range of sleep disorders for centuries. This study aimed to review medicinal plants investigated experimentally or clinically for sleep disorders, as well as their potential mechanisms of action and active components. Electronic databases and literature were systematically investigated to assess all in vitro and in vivo trials and clinical evidence of the efficacy and potential mechanisms of actions playing major roles in sleep induction or insomnia treatment. Among many herbal studies and trials on insomnia, some showed no significant difference between herbal remedies and placebos. While others showed improvements in sleep parameters (sleep latency, total sleep, non-rapid eye movement (NREM) and rapid eye movement (REM) sleep duration, delta activity in NREM sleep, wakefulness anxiety-associated insomnia). In this study, in vitro, animal, and clinical studies investigating a variety of herbal treatments for insomnia were systematically reviewed. The mechanisms of action of herbal medicines in treating insomnia are mainly related to gamma-aminobutyric acid (GABA)-synthesizing and GABA-metabolizing enzymes that influenced sleep outcomes. Overall, herbal remedies were not associated with more benefits than non-benzodiazepines, although side effects were less. The results suggest that herbs have some benefits in improving the quantity and quality of sleep and could be a promising alternative therapy. [GMJ.2019;8:e1085]